Rethinking Criminal Law Policies in Taxation to Overcome Tax Violations - Kusumo, Bambang Ali; Marwiyah, Siti; Yunus, Nur Rohim (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
Taxes are the largest source of state revenue for Indonesia's development, but the tax compliance rate of Indonesians is still low. This study aims to analyze issues related to rethinking criminal law policies in taxation to overcome tax violations. This is normative legal research that uses statutory and comparative approaches. The results of the study show that criminal acts in the field of taxation are included in criminal acts in the field of administrative law, which is known to be simple and flexible in law enforcement as long as the purpose of the law is achieved, namely that taxpayers are willing to pay taxes according to their obligations.